Duvelisib, an oral dual PI3K‐δ, γ inhibitor, shows clinical and pharmacodynamic activity in chronic lymphocytic leukemia and small lymphocytic lymphoma in a phase 1 study. Issue 11 (20th October 2018) - O'Brien, Susan; Patel, Manish; Kahl, Brad S.; Horwitz, Steven M.; Foss, Francine M.; Porcu, Pierluigi; Jones, Jeffrey; Burger, Jan; Jain, Nitin; Allen, Kerstin; Faia, Kerrie; Douglas, Mark; et al.
Abstract: Duvelisib (IPI‐145), an oral, dual inhibitor of phosphoinositide‐3‐kinase (PI3K)‐δ and ‐γ, was evaluated in a Phase 1 study in advanced hematologic malignancies, which included expansion cohorts in relapsed/refractory (RR) chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL) and treatment‐naïve (TN) CLL. Per protocol, TN patients were at least 65 years old or had a del(17p)/ TP53 mutation. Duvelisib was administered twice daily (BID) in 28‐day cycles at doses of 8‐75 mg in RR patients ( n = 55) and 25 mg in TN patients ( n = 18.) Diarrhea was the most common nonhematologic AE (TN 78%, RR 47%); transaminase elevations the most frequent lab‐abnormality AE (TN 33.3%, RR 30.9%); and neutropenia the most common ≥grade 3 AE (RR 44%, TN 33%). The overall response rates were 56.4% for RR patients (1.8% CR, 54.5% PR) and 83.3% for TN patients (all PRs); median response duration was 21.0 months in RR patients but was not reached for TN patients. Based upon phase 1 efficacy, pharmacodynamics, and safety, duvelisib 25 mg BID was selected for further investigation in a phase 3 study in RR CLL/SLL.